Howard S. Becker e gli “approcci moderni” nello studio dei problemi sociali - Rinaldi, Cirus (SocietàMutamentoPolitica, 2018)
The article discusses the intellectual biography of sociologist Howard S. Becker taking into account his contribution to the sociological study of social problems. Becker believes in the possibility of an objective study of the properties of social problems. However he admits that the objective properties of a phenomenon are neither sufficient nor necessary to define something as a “social problem”.